Radiative and mechanical feedback into the molecular gas in the Large Magellanic Cloud: I. N159W - Lee, Min-Young; Madden, S. C.; Lebouteiller, V.; Gusdorf, A.; Godard, B.; Wu, R.; Galametz, M.; Cormier, Diane; Petit, F. Le; Roueff, E.; Bron, E.; Carlson, L.; et al. (Astronomy and astrophysics, 2016)
We present Herschel SPIRE Fourier Transform Spectrometer (FTS) observations of N159W, an active star-forming region in the Large Magellanic Cloud (LMC). In our observations, a number of far-infrared cooling lines, including carbon monoxide (CO) J = 4 → 3 to J = 12 → 11, [CI] 609 μm and 370 μm, and [NII] 205 μm, are clearly detected. With an aim of investigating the physical conditions and excitation processes of molecular gas, we first construct CO spectral line energy distributions (SLEDs) on ~10 pc scales by combining the FTS CO transitions with ground-based low-J CO data and analyze the observed CO SLEDs using non-LTE (local thermodynamic equilibrium) radiative transfer models. We find that the CO-traced molecular gas in N159W is warm (kinetic temperature of 153-754 K) and moderately dense (H2 number density of (1.1−4.5) × 103 cm-3). To assess the impact of the energetic processes in the interstellar medium on the physical conditions of the CO-emitting gas, we then compare the observed CO line intensities with the models of photodissociation regions (PDRs) and shocks. We first constrain the properties of PDRs by modeling Herschel observations of [OI] 145 μm, [CII] 158 μm, and [CI] 370 μm fine-structure lines and find that the constrained PDR components emit very weak CO emission. X-rays and cosmic-rays are also found to provide a negligible contribution to theCO emission, essentially ruling out ionizing sources (ultraviolet photons, X-rays, and cosmic-rays) as the dominant heating source for CO in N159W. On the other hand, mechanical heating by low-velocity C-type shocks with ~10 km s-1 appears sufficient enough to reproduce the observed warm CO.